A study of 18F-FLT positron emission tomography/computed tomography imaging in pediatrics with myeloproliferative neoplasms - Mohamed A. Yassin (16322749) (2021)
Although Myeloproliferative Neoplasms (MPNs) are diseases of the elderly, MPNs are diagnosed in younger age groups in a considerable number of cases. Since most of the available data, as well as current WHO classification criteria, emphasize on the “average” patients with MPNs who range in age between 55 and 65 years. Less consistent data are available in the groups of patients presenting below this median age, such as children and younger adults which we’re planning to reveal. The main purpose of this project to study the uptake pattern of 18FLT-Positron Emission Tomography (PET) and it is value in assessing the malignant hematopoiesis in MPNs within the pediatric age group in terms of diagnosis, staging and monitoring response to therapy. As well as evaluating 18FLT-PET as a novel non-invasive technique in cases with MPNs and its role in comparison to the standard bone marrow biopsy with regard to disease diagnosis, assessment of disease activity, detection of transformation, monitoring of treatment response and grading of fibrosis. Furthermore, we aim to study the association of 18FLT-PET uptake patterns with different genetic makeup (Janus kinase 2, Calreticulin positive, myeloproliferative leukemia protein, or Triple-negative disease) or allele burden in cases of Pre- prefibrotic/early primary myelofibrosis with the ability of FLT-PET to differentiate between Pre- prefibrotic/early primary myelofibrosis and essential thrombocythemia. This trial is registered in ClinicalTrials.gov with number NCT03121599. Protocol version: June 2017 Other Information Published in: Medicine Case Reports and Study Protocols License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1097/md9.0000000000000060